2017
DOI: 10.1097/qai.0000000000001445
|View full text |Cite
|
Sign up to set email alerts
|

The ART Advantage: Health Care Utilization for Diabetes and Hypertension in Rural South Africa

Abstract: Background The prevalence of diabetes and hypertension has increased in HIV-positive populations but there is limited understanding of the role that ART programs play in the delivery of services for these conditions. The aim of this study is to assess the relationship between ART use and utilization of healthcare services for diabetes and hypertension. Methods Health and Aging in Africa: a Longitudinal Study of an INDEPTH Community in South Africa is a cohort of 5,059 adults. The baseline study collects biom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
80
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 86 publications
(87 citation statements)
references
References 30 publications
5
80
2
Order By: Relevance
“…This linkage to care is encouraging and may be important for both future prevention and also older persons’ health and well-being [ 42 , 43 ]. It could result from an ‘ART advantage’ [ 28 ]; these results and other research suggest that linkage to HIV care is associated with diagnosis and treatment of NCDs and other conditions [ 23 , 26 , 28 , 29 , 44 ].…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…This linkage to care is encouraging and may be important for both future prevention and also older persons’ health and well-being [ 42 , 43 ]. It could result from an ‘ART advantage’ [ 28 ]; these results and other research suggest that linkage to HIV care is associated with diagnosis and treatment of NCDs and other conditions [ 23 , 26 , 28 , 29 , 44 ].…”
Section: Discussionmentioning
confidence: 87%
“…Sometimes called an antiretroviral therapy (ART)-advantage, the attachment to health services due to HIV may explain why OPLWH are more likely to know if they have additional chronic conditions and to have it treated, compared to those without HIV [ 25 , 26 ]. Chronic communicable disease, including HIV, has been found to be an important positive predictor of older persons’ healthcare usage and having HIV and being on ART was a positive predictor of being cared for another NCD in two rural South Africa studies [ 27 , 28 ]. OPLWH in rural Uganda had visited a clinic more recently that those who were HIV-negative; these visits were for both HIV and NCD care [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Surprisingly, HIV status was not associated with return for study visits although previous evidence suggests that HIV status is associated with increased contact with various healthcare providers. 38 , 45 Nevertheless, there are different demands for dual protection from an HIV-positive versus HIV-negative population. Although HIV-positive women had higher likelihood of condom use –in line with recommended preventative actions– HIV status did not affect dual protection.…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed similar HIV infection numbers in individuals with and without myocardial infarction and stroke, and an even lower percentage of HIV infected subjects with angina (18.6%) when compared to those without angina (22.9%). These findings might be explained by previous findings from the same cohort that showed that HIV-positive patients are more likely to receive healthcare services for diabetes and hypertension 38 , which ultimately can lead to fewer cardiovascular events.…”
Section: Discussionmentioning
confidence: 82%